Effect of Storage and Processing Methods on the Aroma of Edible Flowers: A Review (Chinese and English versions) - LIANG Zi-jian; YANG Jing-wen; FANG Zhong-xiang (Liang you shipin ke-ji)
Edible flowers are the floral parts of plants that are safe for consumption but have a short shelf life. Due to the interspecific similarity of edible flowers, their aroma properties serve as a vital quality indicator in most commercial flower species. Different parts of edible flowers with characteristic fragrances are widely applied in food products, such as fresh rose petals, hibiscus calyces, dried stigmas of crocus sativus, elderflower syrup, and lavender oil. Terpenes, terpenoids, and phenolics are the common volatile compounds, where the functional groups mainly contribute to the aroma characteristics, including alcohols, aldehydes, ketones, and esters. In fresh edible flowers, most alcohols and esters give a floral and sweet odor, most alkenes are characteristic of a woody aroma, while most aldehydes represent green and citrus scents. Both cold storage (0~4 °C) and modified atmosphere packaging could retain most of the volatiles in edible flowers. Additionally, the total volatile content of edible flowers could be enhanced using various drying technologies. Compared with freeze-drying, hot air drying technologies could generate more volatiles, especially aldehydes. Extraction is a versatile technology to isolate the highest amount of volatile compounds from edible flowers. More alcohols, aldehydes, and ketones are generated by hot water brewing and water-steam distillation. To maintain the original volatile profile, novel extraction technologies such as large-scale headspace collection and condensation processing have been developed and used in recent years. This review provides a reference for the application of edible flowers in the food industry without compromising the odor quality.